TEACHER TRAINING FROM THE PERSPECTIVE OF INCLUSIVE EDUCATION - Lacerda de Caldas Trigueiro, Alexsandra; Lucena de Sousa, Diana (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to reflect on teacher education in the perspective of inclusive education. To do so, it is anchored in the thinking of Brazil (2001), Glat and Nogueira (2002), Mendes (2006) and Silva (2003), among others, aiming at understanding how the insertion of the disabled student occurs in regular school and how if they give the teacher training to serve this clientele. From this academic production, it is possible to contribute to the reflection on inclusive pedagogical practices that should be privileged in the school and from the need for the continued formation of the teacher who opts for inclusive education for all.